PENINGKATAN KEDISIPLINAN MASYARAKAT DALAM BERLALU LINTAS PADA MASA PANDEMI COVID-19 DI WILAYAH HUKUM POLRES MAGELANG - Ruseno, Agris; Akhmad, Jazuli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
Traffic violations committed by motorists while on the road show no traffic discipline. This can cause accidents that are detrimental to motorists on vehicles or goods owned by violators or victims, resulting in serious injury and even death to violators or other road users who are victims of accidents, so research is needed with the aim of identifying the factors that cause low levels of discipline. the community in traffic during the covid 19 pandemic in the Magelang Police jurisdiction, to evaluate these factors causing the low level of community discipline in traffic during the covid 19 pandemic in the Magelang Police jurisdiction, and to formulate efforts to increase community discipline in traffic during the Covid-19 Pandemic in the Magelang Police Legal Area. This research uses qualitative research. The research subjects in this study were 3 members of the National Police at the Magelang Police, while the object of the research was increasing community discipline in traffic during the Covid-19 Pandemic in the Magelang Police Legal Area. In this study using qualitative methods, then using non-statistical data, with the Miles and Huberman method. As a result, the factors that caused the low level of community discipline in traffic during the COVID-19 pandemic in the jurisdiction of the Magelang Police were human factors, psychological factors, vehicle factors, and road environmental factors. Therefore, community discipline in traffic during the Covid-19 Pandemic in the Magelang Police Legal Area continues to be improved with various efforts such as (1) Pre-emptive actions with Traffic education activities (DIKMAS then), Troops Holds Troops and Safety Driving; (2) Preventive actions with Health Protocol Education activities and Distributing Free Masks, Temple Sympathetic Operations and Temple Obedience Operations; (3) Repressive measures to reduce the violation, the Magelang Police carried out several law enforcement actions, including verbal warnings, ticketing and the Gemas Gemilang E-reprimand application. The causes of community discipline in traffic during the Covid-19 Pandemic in the Magelang Police Legal Area still need to be improved due to lack of understanding of traffic regulations, readiness of self and vehicles used, responsibility for the safety of self and others, prudence and vigilance, the space for activities is limited due to the Covid 19 pandemic, temple-compliant operations which should also be able to overcome violations of the Traffic and Road Transport Law, efforts made to increase community discipline in traffic during the Covid-19 Pandemic in the Magelang Police Legal Area by education and socialization, intensifying the implementation of the Temple Obedient Operation but still complying with health protocols, there is a need for creativity in the use of technology, for example social media.